Comparative prognostic impact of ACCI and AHEAD risk score in heart failure with reduced, mid-range and preserved left ventricular ejection fraction admitted for acute decompensated heart failure. (25th November 2020) - Kayama, K; Yamada, T; Watanabe, T; Morita, T; Furukawa, Y; Tamaki, S; Kawasaki, M; Kikuchi, A; Kawai, T; Seo, M; Nakamura, J; Kawahira, M; et al.
Abstract: Background: Comorbidities are strongly associated with poor clinical outcome in heart failure patients (pts). The Age-adjusted Charlson comorbidity index (ACCI), which is well-known widely used comorbidity index, recently has been used as a robust prognostic model in heart failure pts. On the other hand, AHEAD risk score has been recently reported as a useful long-term risk stratification score in acute decompensated heart failure (ADHF) pts. Recently, a new group of heart failure pts with mid-range ejection fraction (HFmrEF) has been defined, separated from reduced ejection fraction (HFrEF) and preserved ejection fraction (HFpEF). We sought to compare the prognostic value of ACCI and AHEAD score in ADHF pts, relating to HFrEF, HFmrEF and HFpEF. Methods: We prospectively studied 410 consecutive ADHF pts (HFrEF [n=143], HFmrEF [n=99] and HFpEF [n=168]) with survival discharge. ACCI contains 19 issues which was weighted according to their potential influence on mortality. AHEAD risk score is a simple index, which is range 0–5; atrial fibrillation, hemoglobin <13 mg/dL for men and 12 mg/dL for women, age >70 years, creatinine >130 μmol/L, and diabetes mellitus. The endpoint of this study was all cause death (ACD). Results: During a follow-up period of 2.4±1.4 years, 119 pts had ACD (42, 29 and 48 pts in HFrEF, HFmrEF and HFpEF, respectively). At univariate Cox analysis, ACCI and AHEAD risk score were significantly associated with ACD in each subgroup. At multivariate Cox analysis, in HFrEF pts, ACCI, but not AHEAD risk score, showed the significant and independent association with ACD. In HFmrEF, both ACCI and AHEAD risk score was significantly and independently associated with ACD and ROC analysis showed AUC of ACCI was greater than that of AHEAD risk score (0.778 [0.683–0.855] vs 0.637 [0.572–0.764], p=0.07). On the other hand, in HFpEF pts, AHEAD risk score, but not ACCI, showed the significant and independent association ACD. Conclusion: ACCI provides more prognostic value in HFrEF pts, and AHEAD risk score has more prognostic value in HFpEF pts. In HFmrEF pts, both ACCI and AHEAD score might have prognostic values, although ACCI tends to be more associated with ACD than AHEAD score. Funding Acknowledgement: Type of funding source: None